2017
DOI: 10.1364/ol.42.003694
|View full text |Cite
|
Sign up to set email alerts
|

Optical parametric generation in orientation-patterned gallium phosphide

Abstract: We report the first optical parametric generator (OPG) based on the new nonlinear material, orientationpatterned gallium phosphide (OP-GaP). Pumped by a Qswitched nanosecond Nd:YAG laser at 1064 nm with 25 kHz pulse repetition rate, the OPG can be tuned across 1721-1850 nm in the signal and 2504-2787 nm in the idler. Using a 40-mm-long crystal in single pass, we have generated a total average output power of up to ~18 mW, with ~5 mW of idler power at 2670 nm, for 2 W of input pump power. The OPG exhibits a pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 14 publications
(13 reference statements)
3
6
0
Order By: Relevance
“…Since the OP-GaP crystal end-faces are AR-coated for high transmission (R<1%) at 1064 nm and 1500-1900 nm, with >80% transmission over 2500-2800 nm, the major contribution to the drop in the transmission at the interacting wavelengths is associated with the absorption and propagation losses in the bulk crystal. We also observed that the transmission of the crystal was dependent on the operating temperature, as reported previously [17,21]. The low crystal quality, operating at a pump wavelength close to the band edge and the temperature dependence of the absorption could be attributed to the Urbach tail or free-carrier absorption in OP-GaP.…”
Section: Power Scalingsupporting
confidence: 85%
See 1 more Smart Citation
“…Since the OP-GaP crystal end-faces are AR-coated for high transmission (R<1%) at 1064 nm and 1500-1900 nm, with >80% transmission over 2500-2800 nm, the major contribution to the drop in the transmission at the interacting wavelengths is associated with the absorption and propagation losses in the bulk crystal. We also observed that the transmission of the crystal was dependent on the operating temperature, as reported previously [17,21]. The low crystal quality, operating at a pump wavelength close to the band edge and the temperature dependence of the absorption could be attributed to the Urbach tail or free-carrier absorption in OP-GaP.…”
Section: Power Scalingsupporting
confidence: 85%
“…Recently, we also demonstrated a tunable DFG source based on OP-GaP operating across 2548-2781 nm by mixing the input pulses from a Q-switched nanosecond Nd:YAG pump laser at 1.064 μm with the tunable signal from a MgO:PPLN pulsed OPO in a 40-mm-long crystal, providing up to ~14 mW of average output power at 80 kHz repetition rate [16]. In another report, we demonstrated an optical parametric generator (OPG) based on OP-GaP pumped directly by a Q-switched Nd:YAG laser at 1.064 μm [17]. The OPG was temperature-tuned across 1721-1850 nm in the signal and 2504-2787 nm in the idler, providing up to ~18 mW of the total average output power at 25 kHz repetition rate, with ~5 mW of the idler output power.…”
Section: Introductionmentioning
confidence: 99%
“…However, the signal wavelengths for the pump power of 4.2 W are 8-12 nm shorter than those for the pump power of 1.2 W at each temperature across the tuning range. Given the signal tuning rate of 0.7 nm/ºC, this means that the internal temperature of the OP-GaP crystal pumped at 4.2 W is about 11-17 ºC higher than when pumped at 1.2 W, indicative of significant thermal effects in the OP-GaP crystal, which is attributed to strong pump absorption, as also observed previously [17]. In addition, due to reduced thermal effects, signal and idler wavelengths obtained with 1.2 W pump power are closer to the theoretical tuning curves calculated from the relevant Sellmeier equations [15], represented by the solid lines in Fig.…”
supporting
confidence: 71%
“…We also reported a pulsed nanosecond mid-IR source based on difference-frequency-generation (DFG) in OP-GaP, providing tunable output across 2548-2781 nm, with highest average power of 14 mW at 2719 nm at 80 kHz repetition rate [16]. We further demonstrated optical parametric generation (OPG) in OP-GaP pumped by a nanosecond Nd:YAG laser at 25 kHz, resulting in a highest total power of ~18 mW and a temperature tuning range of 1721-1850 nm for signal and 2504-2787 nm for idler [17]. In this letter, we describe what we believe to be the first nanosecond pulsed OPO in singly-resonant oscillator (SRO) configuration based on OP-GaP.…”
mentioning
confidence: 93%
“…DFG and optical parametric generation (OPG) have been demonstrated with nanosecond and picosecond pulse 1-µm lasers [28][29][30], but the mid-IR wavelengths generated were around 3 µm, which fails to take advantage of OPGaP's transparency range up to 12 µm. DFG between continuous-wave lasers was used to generate 3.40 µm [31] and 5.85 µm [32] in OPGaP.…”
Section: Introductionmentioning
confidence: 99%